2003
DOI: 10.1152/jn.00563.2002
|View full text |Cite
|
Sign up to set email alerts
|

Directional Sensitivity of Neurons in the Primary Auditory (AI) Cortex: Effects of Sound-Source Intensity Level

Abstract: Transient sounds were delivered from different directions in virtual acoustic space while recording from single neurons in primary auditory cortex (AI) of cats under general anesthesia. The intensity level of the sound source was varied parametrically to determine the operating characteristics of the spatial receptive field. The spatial receptive field was constructed from the onset latency of the response to a sound at each sampled direction. Spatial gradients of response latency composing a receptive field a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 69 publications
2
20
2
Order By: Relevance
“…Previous studies in auditory cortex of cats have shown that response latency varies with sound location, and have suggested that temporal information might be used as part of the code for sound location (Middlebrooks et al, 1994Brugge et al, 1996Brugge et al, , 1998Brugge et al, , 2001Eggermont, 1998;Eggermont and Mossop, 1998;Xu et al, 1998;Brugge and Reale, 2000;Furukawa et al, 2000;Jenison et al, 2001;Furukawa and Middlebrooks, 2002;Reale et al, 2003;Stecker et al, 2005b). We confirmed that first spike latency varies with sound location in primate auditory cortex as well.…”
Section: Latency Of Response and Sound Locationsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies in auditory cortex of cats have shown that response latency varies with sound location, and have suggested that temporal information might be used as part of the code for sound location (Middlebrooks et al, 1994Brugge et al, 1996Brugge et al, , 1998Brugge et al, , 2001Eggermont, 1998;Eggermont and Mossop, 1998;Xu et al, 1998;Brugge and Reale, 2000;Furukawa et al, 2000;Jenison et al, 2001;Furukawa and Middlebrooks, 2002;Reale et al, 2003;Stecker et al, 2005b). We confirmed that first spike latency varies with sound location in primate auditory cortex as well.…”
Section: Latency Of Response and Sound Locationsupporting
confidence: 86%
“…One such possibility has been that spike timing information might encode sound location (Middlebrooks et al, 1994). Evidence that first spike latency and/or the temporal pattern of the response varies with sound location has been reported in cats and ferrets (Middlebrooks et al, 1994Brugge et al, 1996Brugge et al, , 1998Brugge et al, , 2001Eggermont, 1998;Eggermont and Mossop, 1998;Xu et al, 1998;Brugge and Reale, 2000;Furukawa et al, 2000;Jenison et al, 2001;Furukawa and Middlebrooks, 2002;Reale et al, 2003;Mrsic-Flogel et al, 2005;Stecker et al, 2005b). This has also been shown to be true for awake cats .…”
Section: Relationship To Previous Neurophysiological Studiesmentioning
confidence: 94%
“…Instead, it is sufficient to have a mechanism that simply counts the number of spikes in the response, and marks their mean time. The feasibility of a decoding scheme based on spike latency has been discussed by others (Brugge et al, 2001;Furukawa and Middlebrooks, 2002;Jenison and Reale, 2003;Reale et al, 2003).…”
Section: Implications For the Neural Codementioning
confidence: 99%
“…Unilateral lesions of the auditory cortex have been shown to produce deficits in contralesional space in a variety of species (1)(2)(3)(4), indicating a critical role for auditory cortex. However, despite considerable effort to determine how the cerebral cortex processes acoustic space, our understanding remains rudimentary (e.g., [5][6][7][8][9][10][11][12][13][14][15][16][17]. From these studies and others, we know that (i) acoustic space is not topographically organized in the mammalian cerebral cortex and (ii) single neuron spatial receptive fields are very broad and, in themselves, unlikely to account for localization ability.…”
mentioning
confidence: 99%